Proportionality Principle on Online Lending Contract in Indonesia - Chesa Ramadhan; Adimas Rakyandani Saksono (Fakultas Hukum Universitas Airlangga, 2019)
AbstractOnline lending is form of alternative funding resulted from financial technology innovation. Until February 2019 there are 99 financial technology corporations that engaged in lending activity that operated officially, legally, and recognized by Otoritas Jasa Keuangan. However, many problems arise form this innovation in form of online lending. Many consumers became the victims of either illegal or even legal online lending platforms. Started from the paramount loan interest applied in the online lending agreement until the amount of loan that need to be paid did not in accordance to the initial amount of debt, become core of the problems for the online lending consumers that treated unfair and unjustly by the online lending platform organizer. Moreover, online lending contract commonly belonged to the standard clause agreement that have been pre-arranged by one of the contracting parties. This research has purpose to determine the urgency of application of the proportionality principle on online lending contract. This research using doctrinal research method followed by conceptual and statute approaches. This research expected to generates conclusion on the notions of application of proportionality principle on online lending contract that included as standard clause contract in order to distribute contracting parties’ rights and obligations proportionally. Therefore, in future the online lending agreement could generate justice and proportional contract for contracting parties and the substance of the contract can reflect this proportionality principle.